Effect of irradiation of ultraviolet on the quantitation method of enhanced green fluorescent protein - Chee Heng, Hor (2015)
In last 30 years, green fluorescent protein (GFP) has changed from an unknown protein to a commonly used protein in bioscience application due to its visible fluorescence. As the usage of GFP increases, fluorescent detection and measurement devices are becoming more important. To detect and measure the GFP, a gel-based imaging system using a native polyacrylamide gel was developed. The ultimate aim of this study is to investigate the effect of ultraviolet (UV) light on the GFP quantitation method. In the research, enhanced GFP (EGFP) was expressed in Escherichia coli strain BL21(DE3) and purified using immobilized metal ions affinity chromatography. Different dilution of EGFP was prepared and their concentrations were determined by Lowry’s method using bovine serum albumin as the standard. The EGFP dilution samples were then loaded into a native polyacrylamide gel. After electrophoresis, fluorescent image of EGFP on the gel was captured using gel imaging system under different UV irradiation exposure period. The UV irradiation has a marked influence on the EGFP fluorescence intensity. The fluorescence intensity was increased as the UV exposure period increased from 5-35 s. However, the fluorescence intensity decreased when the exposure period was increased further. Highest fluorescence intensity happened at around 35 s of UV exposure. By using different concentration of purified EGFP, the photobleaching process followed a first order reaction with rates between 3712-8213 int/s. The linearity showed insignificant change and lied within 0.922-0.946. It became more reliable when the UV exposure time increases. However, UV exposure time affected the fluorescence intensity, it is better to choose around 35s as UV exposure time due to highest fluorescence intensity when using gel-based imaging method as quantitation method. Key words: GFP, EGFP, UV, gel-based imaging method, quantitation